Functional properties of proteins isolated from industrially produced sunflower meal - Petia Ivanova; Vesela Chalova; Lidia Koleva (International Journal of Food Studies)
Protein isolate 1 (PI1) and protein isolate 2 (PI2) were prepared from industrially produced sunflower meal by using isoelectric and ethanol precipitation respectively. The water absorption capacity of PI1 was 6 times higher than that of PI2 and was significantly reduced by the presence of 0.03 M and 0.25 M NaCl. Oil absorption capacity of both protein isolates was not influenced by NaCl supplementation. Foam capacity of PI1 and PI2 was pH-dependent. While the foam capacity of both isolates was improved by either 0.03 M or 0.25 M NaCl, the foam stability was negatively influenced by the addition of NaCl at all pH values with except for pH 4. Emulsifying activity of PI1 and PI2 was lowest at pH 4. The emulsions exhibited relatively high stability (> 90%) under all studied conditions. Knowledge of the influence of pH and boundary concentrations of NaCl on the functionality of sunflower meal protein isolates could be beneficial for their future potential application in food industry.